Analisis Dampak Kinerja Konsultan Manajemen Konstruksi pada Ketepatan Biaya dan Waktu Pembangunan Lapas Bagansiapiapi - Siregar, Zulfikar; Rita, Eva; Khadavi, Khadavi (Jurnal Talenta Sipil, 2025)
In the construction of Bagansiapiapi prison, there was a critical progress of the work caused by decreasing labor productivity, lack of equipment, and changes in the schedule plan for ready-mix concrete casting materials. The final completion of the physical construction work of Class IIA Bagansiapiapi Prison was delayed by 5 days from the initial contract of 165 calendar days. Therefore, the purpose of this study was to determine the dominant indicators of the Construction Management Consultant regarding the suitability of the cost and completion time of the Bagansiapiapi Prison Construction work. This research method is quantitative descriptive by distributing questionnaires with a Likert scale to respondents involved in the construction project as many as 87 respondents and then testing the validity, reliability and factor analysis. The results of this study indicate that the dominant indicator of the suitability of the cost of completing the Bagansiapiapi Prison Construction work is the accurate price estimation component with a correlation value of 0.856. Then, the dominant indicator of the suitability of the completion time of the Bagansiapiapi Prison Construction work is the material/equipment procurement schedule with a correlation value of 0.895.